Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Num Pages: 8
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Num Pages: 1
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Num Pages: 11
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Num Pages: 30
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Cultural Polysemy and Vernacular Cosmopolitanism in the Theme Songs of Hong Kong Television Dramas - Kai Khiun, Liew (Television Histories in Asia, 2015)
In 1980, Hong Kong’s commercial Television Broadcast Limited (TVB) television drama The Bund ( 上海滩 ) was popularly received in the city as well as in South-East Asia and the broader Chinese diaspora. Set in the cosmopolitan treaty port of Shanghai in the 1920s, The Bund revolves around the violent ascent of a coolie (Ray Lui) and a disillusioned student activist (Chow Yun-Fat) to become prominent mobsters. Not only were two sequels made within that year, but this historical gangster drama has been repeatedly resurrected in television dramas and fi lms, including Chow’s redux, The Last Tycoon ( 大上海 ), three decades later in 2012. From karaoke lounges to social media sites, theme songs of The Bund remain popular more than three decades after the dramas were screened . With music composed by Joseph Koo, lyrics by Wong Jim and sung by Frances Yip, the main and supplementary theme songs refl ected the intimate role of the Hong Kong-based contemporary Cantonese popular music, or Canto-pop, in cultivating a more memorable and enduring televisual culture. With the smooth synchronization of Koo’s classical music with the undulating pitch of Yip, the song articulates the unpredictable tribulations of the changing fortunes in the treaty-port of Shanghai in the interwar years. To a certain extent, it is also a narrative that reminds viewers in Hong Kong and beyond of similar socio-political and historical predicaments.
Num Pages: 18
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

Dramatizing the Nation: Television, History and the Construction of Singaporean Identity - Tay, Jinna (Television Histories in Asia: Issues and Contexts, 2015)
Television dramas, both serials and series, have been a long-term recruiter of large-scale national audiences for television broadcasters as they are potentially able to speak to their audience in affective and imaginative ways (Chan 2011 ; Sun and Gorfi nkel 2014). Usually it is the locally produced drama that resonates most with a national audience, the familiarity of the setting and context often carrying signifi cant implications for social and sometimes political life (Blandford et al. 2011 , Chan 2011 ). These television texts can pick up on popular strands of discourses in the public sphere and succeed in establishing a form of dialogue with audiences; in the instances examined in this chapter, this dialogue is about the formation of national identities or citizenships. There is good reason, then, for broadcasters and governments to attempt to use television drama to educate and persuade, although Sugg and Power ( 2011 : 26-7), long-term drama producers at the BBC World Service Trust, warn that for dramas to succeed in this manner, they first have to be entertaining, otherwise they are unlikely to generate an audience in the fi rst place. Audiences are not easily fooled and can sniff out the difference between being entertained and being preached at in a didactic way. This chapter deals with a period in the history of Singapore where television historical drama played a signifi cant role in creating a national past upon which the promotion of a distinctive national identity might be based. In addition to a consideration of a selection of drama series themselves, the chapter draws upon interviews where viewers are encouraged to share their memories of these dramas, and the part they played in the construction of a Singaporean identity.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Sange ThakunBangla News Channels and Media-Citizenry - Gupta, Nilanjana (Channeling Cultures: Television Studies from India, 2014)
With special reference to the current scenario in West Bengal, this chapter argues that the rise and popularity of Bangla news channels like Star Ananda, 24 Ghanta, Kolkata TV, and Tara News have resulted in the emergence of a vernacular style of news broadcasting which is quite distinct from that of global or national news media. One major point in this chapter is how the vernacular news channels encourage particular forms of address — the emotional, the intimate and the melodramatic — and how close-ups and sound bites create particular kinds of telegenic political leaders who can use these formal characteristics to their advantage. This chapter explores the ways in which a distinctive kind of vernacular is reconfiguring the nature of political participation itself and hence the notion of citizenship and perhaps even the nature and functioning of the nation-state in India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

From Clients to Consumers: The Missing Citizens among the Indian Television Audience - Sinha, Dipankar (Channeling Cultures: Television Studies from India, 2014)
Beneath many instances of ’sweeping’ change, both structural and representational, in the market-dominant, liberalized and privatized Indian televisual scenario there lies a hidden transcript of continuity insofar as the encoding of development issues, images and messages is concerned. In the periods of Doordarshan and later corporate channels, though with markedly different historical contexts, reference points, contents and styles — the encoding of ’development’ leaves little autonomy to the audiences. In a political slant indicating how the two televisual periods converge in contracting the space for public debate and civic engagement the essay seeks to make a departure from the dominant view which puts them in binary positions.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

TV after Television Studies: Recasting Questions of Audiovisual Form - Roy, Abhijit (Channeling Cultures: Television Studies from India, 2014)
This chapter locates India, and broadly the post-colonial context, within the larger debates concerning television’s audiovisual form and mode of address. It tries to demonstrate that certain key traits in Indian popular performative traditions, representing an ‘alternative’ negotiation with modernity, are somewhat homologous with what western theorists have tried to specify (though in contradicting terms) as the features of televisual mode of address and ‘flow’. The chapter reads the specific imports of this correspondence in histories of Indian television with special reference to a somewhat novel way television has started imagining the nation after liberalization. The significance of the Indian popular film form as lending a major legacy to tele-viewership in India constitutes a major strand of argument.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Reformatting the Format: Philippines in the Global Television Format Business - Santos, Joseﬁna M. C. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In the eyes of many observers the Philippine cultural icon that is synonymous with travel, as well as being the subject of numerous advertisements is the jeepney, a public-transport vehicle assembled in the style of the US military jeep but lengthened to accommodate from fourteen to twenty-two sitting passengers. What distinguishes the jeepney from run-of-the-mill public transport however is its artistic décor: a clutter and kaleidoscope of various artefacts from miniature steel horses dotting the hood, to massive, jazzy plastic or steel billboards announcing the name of the jeepney, to murals painted in ﬁesta colours at the sides, to a bizarre combination of items in the front windshield juxtaposing conﬂicting images of the Sto. Nino (the baby Jesus Christ) and stickers with sexually risqué messages.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Num Pages: 16
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Let the Contests Begin! ‘Singapore Slings’ into Action: Singapore in the Global Television Format Business - Lim, Tania (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Why is the hit Singapore edition of Who Wants To Be A Millionaire? must-see TV?1. Watch it so that you can hold the ‘hottest topic’ with your friends. 2. So you can be encouraged by the courage of some contestants who are bold enough to brave national TV when apparently they have not read enough. 3. So you can judge for yourself if you are bold (and knowledgeable) enough to brave national TV for your possible 1st million. 4. So you can call the number on screen and make your 1st million. 5. Finally, watch it to see for yourself that Singaporeans are not as well read and as globalized as we all think we are.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Coping, Cloning and Copying: Hong Kong in the Global Television Format Business - Fung, Anthony (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Hong Kong is famous internationally as a ﬁnancial market, a shopping paradise, and Chinese ﬁlm production hub, but notoriously (and perhaps even attractively for some) Hong Kong is also a hotbed of piracy of computer software, DVDs, watches and toys.1 While many cultural products such as television dramas and movies are original and quite reputable in the region, media critics argue that the copycat phenomenon, which includes borrowing, inserting and modifying other cultural texts to augment local production, is common in the media and entertainment industries (Fung 1998). Whenever a new form, style, or popular culture trend emerges in Hong Kong, market forces soon kick in to replicate it. However, this kind of reproduction, as shown by the history of cultural production in Hong Kong, does not necessarily lead to a degradation of programme quality. Reproduction is not only a savvy strategy to reduce the ﬁnancial risks inherent to new products, but also aims at producing ‘improved’ versions which can reap more proﬁts for the industry.
Num Pages: 14
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Cloning, Adaptation, Import and Originality: Taiwan in the Global Television Format Business - Liu, Yu-Li; Chen, Yi-Hsiang (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Taiwan residents enjoy one of the most abundant television diets in East Asia. Eighty per cent of households subscribe to cable television services, offering a buffet of more than eighty channels including niche and full service channels. Taiwan’s television industry, while relatively small in comparison with its competitors in East Asia, has established a reputation for creatively re-generating formats developed elsewhere.
Num Pages: 20
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

A Local Mode of Programme Adaptation: South Korea in the Global Television Format Business - Lee, Dong-Hoo (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television has been called ‘a Western-originated project’ (Barker 1997: 5) and an institution of Western capitalist modernity. The global circulation of Western-centred, or more speciﬁcally, American-centred cultural products, contributes to the formation and dissemination of a global shared culture that reaches across the boundaries of nation-states. In the process American cultural products play a role in the formation of local television cultures.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Corée du Sud (corpus analysé); Corée du Sud (lieu de production du savoir); _Nettoyé

Feeling Glocal: Japan in the Global Television Format Business - Iwabuchi, Koichi (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In March 2001 a Japanese newspaper report entitled ‘Indians are addicted to a quiz show’ drew attention to a phenomenally popular television programme in India – a quiz show that attracts millions of viewers in which challengers strive to win prize money (Asahi Shinbun 2001). What was particularly eye-catching for the journalist was the proﬂigately decorated studio set located in Mumbai (Bombay) and the caring guidance of the MC, a ﬁlm star famous in India. The name of the show, as you might have already inferred, was Who Wants To Be A Millionaire?.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Japon (corpus analysé); Japon (lieu de production du savoir); _Nettoyé

Television and Dating in Contemporary China: Identities, Love and Intimacy - Yang, Chao (Palgrave Macmillan Singapore, 2017)
"This book considers the changing nature of intimacy in contemporary China, providing a unique case study of romantic subjectivities in young people in the world's fastest growing economy. Since the implementation of reform in 1978, the economic and socio-cultural environment of modern China has experienced a dramatic transformation under the influence of urbanization and globalization, facilitating more individualized identity among Chinese youth. This book bridges the gap between an emergent emphasis on individualisation and the country's traditional norms and values. It focuses on young people's understandings of various forms of relationships such as cohabitation, extramarital relationships and multiple relationships, suggesting a challenge to traditional familial values and an increasingly diversified understanding of the concepts of love and romance. By examining the formation of relationships among 21st century Chinese youth, notably through the lens of popular Chinese TV dating programs, this book considers how dating and relationships mirror China's changing societal structure and examines social and cultural transformations in Chinese society."
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Film and Television Culture in China - Zhifeng, Hu (Paths International, Limited, 2018)
Film and Television Culture in China gives a provocative analysis of film and television culture in China. The author first gives a panoramic picture of Chinese culture in which film and television was born and shaped. He then delineates the definition, composition, and basic relations in film and television culture. Also discussed are the two traditions in Chinese film and television culture–the worldly spirit and the poetic style. The two traditions are deeply rooted in Chinese Confucianism and Taoism, and have influenced Chinese film and television from the start. The author provides in-depth and original readings of the phenomena in Chinese film and television culture, such as: the reform films and the reflection films; the character and mission of television documentary; and a dialogue between the mainland and Taiwan. Film and Television Culture in China will be an essential guide to understand the film and television culture in China, from early screen to the present day.
Keywords: 1-Cinéma; 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

TV China: Control and Expansion - Zhu, Ying (The Routledge Companion to Global Television, 2019)
The chapter traces the evolution of Chinese television since 1958 from a state propaganda organ to a profit-generating media juggernaut, with China Central Television (CCTV) as the only network TV responding to both market principles and party directives. Commercialization and marketization played a major role in the rapid development of the Chinese television industry. In recent years China’s TV industry has witnessed the rise of private media companies and the rapid expansion of digital media and the proliferation of over the top (OTT) content. The chapter further provides an overview of China’s overall TV structures and teases out the relationship between CCTV and local stations. The most popular genre on Chinese TV is serial drama, which developed from predominantly single-episode anthology dramas in the 1980s to chiefly multi-episode serial dramas. Talk shows and reality TV became fashionable since the late 1990s.
Num Pages: 9
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Chine (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé; États-Unis (lieu de production du savoir)

Arab Television Industries: Enduring Players and Emerging Alternatives - Khalil, Joe F. (The Routledge Companion to Global Television, 2019)
This chapter provides an overview and analysis of emerging alternatives in the context of Arab television production, programming, and distribution. Media convergence and the access to digital technologies have accentuated the fragmentation of audiences, revenue streams, and forced alliances and competitions between previously discrete sectors of the media business. Yet, alternative practices are closely associated with changing political, economic, and cultural vectors in the Arab region and the increasing integration of its television industries in global media. The chapter argues that these alternatives constitute a set of continuities with the history of Arab television. Taken together, they also demonstrate some level of transformation in production practices, programming strategies, and distribution operations.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

The Social and Political Dimensions of Global Television Formats: Reality Television in Lebanon and Saudi Arabia - Kraidy, Marwan (Global Television Formats: Understanding Television Across Borders, 2012)
When scholars and policy makers contemplate the Arab “media revolution,” they mostly think of Al-Jazeera and its news competitors. They are guided by the assumption that all-news satellite television networks are the predominant, even the single, shaper of the Arab public sphere, a perspective exacerbated by the September 11, 2001 attacks. Drawing on a larger work (Kraidy, 2009, forthcoming), this chapter presents an alternative view, emphasizing instead the combined impact of Arab entertainment television and small media such as mobile phones on Arab governance. It explores how entertainment television is an active contributor to shaping what Arab publics discuss and do in both the social and political realms. As local (in this case regional/pan-Arab, reaching two dozen Arabic-speaking countries) adaptations of global television formats, Arab reality television shows exhibit a combination of signs and practices from several worldviews. As such, this chapter will show how Arab reality shows are open to multiple processes of appropriation and redeployment. Though numerous scholars have for years studied the differentiated “reception” of television texts in various contexts, this chapter focuses speciﬁcally on television formats in a context of growing media convergence and protracted political instability and social upheaval. Speciﬁcally, it focuses on reality television’s social and political impact, which stems primarily from its activation of new communication processes between a variety of information and media technologies creating what I call “hypermedia space.” In the new Arab information order, reality television activates hypermedia space because it promotes participatory practices like voting, campaigning and alliance building, via mobile telephones and related devices.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Arabie Saoudite (corpus analysé); Liban (corpus analysé); Qatar (lieu de production du savoir); _Nettoyé

Is the Video Game a Cultural Vehicle? - Chen, Chi-Ying (Games and Culture, 2013)
Following the exportation of Japanese media products such as TV dramas, Japanese culture and products have swept across many Asian countries, especially Taiwan. Based on the historical background and unique characteristics of games, this study investigates the cultural effect of Japanese video games on players in Taiwan. This study also presents an analysis of the differences between TV and the video game as cultural vehicles. We used both quantitative and qualitative methods. Results indicate a relationship between game-playing behavior and the identification of Japanese culture. However, the relationship between video game playing and consumption was nonsignificant. This shows the power of video games in nation-building but not in nation-branding, in contrast with TV. This study presents a discussion of the findings to shed light on the cultural effects of video games.
Keywords: 1-Jeux vidéo; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À nettoyer; _À vérifier-Télé

From Separation to Integration: Identity Development of Korean Adult Players in Online Game World - Doh, Young Yim; Whang, Sang-Min Leo (Games and Culture, 2014)
This research examined the identity development of Korean adult players in the online game world. Q methodology was used to investigate the subjectivity of self-development in Mabinogi (Massive Multiplayer Online Role-Playing Game). Thirty-seven adult players sorted 57 behavior statements to reflect the changes in their behaviors from past to present. Three types of self-development were found: achievement-oriented development, control-oriented development, and relational development. The behavior patterns of these three types were compared to identify similarities and differences among them in terms of psychological meanings and values in the online game life. The results illustrate that the online game world can be defined as a new behavioral setting, made possible by digital technology, in which individuals are able to experience three different paths of identity development.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Cultural History of Online Games in China, 1995–2015 - Chew, Matthew M. (Games and Culture, 2016)
This study critically assesses the Chinese online games industry through problematizing the creativity of Chinese games. I find that between 1995 and 2001, Chinese online games were mostly developed by amateurs, noncommercial, and considerably creative. Between 2002 and 2005, industrial growth allowed some room for local creativity despite commercialization and dominance of imported games. Current scholarly, business, and media discourses unfairly ignore creativity in these first two periods and yet praise the Chinese game industry’s commercial success since the late 2000s. I challenge these discourses by illustrating that between 2006 and early 2009, a new, ethically dubious, and uniquely Chinese business model emerged, became domestically dominant, and quietly and profoundly impacted on global online game design. From mid-2009 to 2015, there is ongoing corporatization based on the dubious Chinese business model on the one hand, and a reemphasis on creativity motivated by browser and mobile game formats on the other.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games With a Continuum: Globalization, Regionalization, and the Nation-State in the Development of China’s Online Game Industry - Jiang, Qiaolei; Fung, Anthony Y.H. (Games and Culture, 2019)
As a case study, this article examines the development of China’s online game industry and how China responds to the forces of globalization. Based on in-depth interviews, ethnographic research, and the analysis of archive documents from the past few years, this study identifies China’s evolving strategy of neo-techno-nationalism. In the Chinese context, this national strategy manipulates technology to create a version of popular nationalism that is both acceptable to and easily censored by the authorities. Therefore, cultural industries that adopt this strategy stand a good chance of prevailing in the Chinese market. This success explains why the regional competitors of Chinese online games—Korean games—are more successful in China than most of their Western counterparts. By providing a snapshot of the current ecology of China’s online game industry, this article also discusses the influence of regional and global forces in a concrete context and argues that the development of China’s online game industry depends more on political factors than economic factors.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"–Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Games Studies India Adda Talk #9: Lakshmi Menon - Game Studies India Adda (Game Studies India Adda, 2021)
Unreal City: Expressions of Tokyo in Video Games Abstract: Games today, with advancements in graphic design and capability of the platforms on which they can be played, are almost akin to interactive films- in which the player not only consumes the movie-like storyline, but becomes an active participant in the narrative and its outcomes. Worldbuilding in video games has strong connections with the approaches contained in semiotics, as it is not with the images on the screen that players interact, but rather the world that is represented by the images. I intend to examine Tokyo as a virtually constructed game world in three separate texts – Atlus Studios’ Persona 5, Sega’s Yakuza series and Square Enix’s The World Ends with You. The fictionally created cityscapes of contemporary Japan have become ideal spaces for the video games to propagate, their construction in the texts can be seen a form of techno-orientalism that is simultaneously rooted in both Eastern and Western imagination. Each of these texts constructs its own version of Tokyo that, while being recognisable through the use of specific semiotic markers, is also sufficiently different enough to make it a virtual, unreal, space. However, what must be noted is that this space only exists in its entirety when it is interacted upon by the player. Using Lefebvre’s conceptualisation of social space into spatial practice, representations of space and representational space, this paper seeks to look at how the construction of the digital city is not merely a 3D representation thereof, but points where interactivity and narrative coincide. It is through the locus of these two elements that the player comprehends and navigates game narratives. My purpose will therefore be to look at the constructions of Tokyo within video games as data visualisations of spaces that become places through interactivity and comprehension of the player. About Laxmi: Lakshmi Menon is Assistant Professor of English at VTM NSS College, Trivandrum, and a PhD candidate at the Centre for English Studies, Jawaharlal Nehru University, where her thesis is a study of Harry Potter slash fanfiction and fan communities. She is currently researching Boys Love fan cultures in South Asia, while her wider research interests also include digital humanities, popular culture and queer literature.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Game Studies India Adda Talk #8: Prabhash Tripathy - Game Studies India Adda (Game Studies India Adda, 2021)
What/Who is playing Cyborg: An investigation of the 'Gamer' as a figure - Prabhash Ranjan Tripathy The current talk is an exploration into the question as to whether the gamer figure that emerged in India in the 1990s can be thought of as a cyborg and if so, then what kind of cyborg is the gamer? Can one think of the gamer-cyborg as a posthuman liberatory figure or is the gamer-cyborg still all too human? The intent of the paper in asking these questions and problematizing the figure of the Gamer is to launch an investigation into the more pressing question that one encounter in the wake of the cyber/information-turn, that is, how does one contemplate, comprehend, and articulate the 'new' in the identities that are formed and acquired with the advent of what has been identified as the cyber/information turn in culture? Can the connection between biological and technological be the sole basis for considering figurations like the Gamer as something new? Can they be thought of as a new subjectivity, a new politics, a new relationship to power? Is this 'new' democratic, free of discrimination and based on an egalitarian principle or is the 'new' an optimization of old and existing structures and modes of oppression? Bio: Prabhash Ranjan Tripathy was born in Odisha, India. He completed his B.A. (Hons) English, M.A. in English literature and M.A. in Comparative Indian Literature from University of Delhi. He is currently a PhD scholar at the school of Arts and Aesthetics, Jawaharlal Nehru University. Has submitted his MPhil dissertation titled ‘Playing Cyborg: A study of the Gamer in the Videogame Parlours of Delhi and Mussoorie’, following which was a doctoral fellow at the International Research Centre “Interweaving Performance Cultures” and is currently working on his PhD dissertation titled ‘Between WorkStation and PlayStation: The Cultural Location of Videogames in India’. Interest areas include Superhero comic books, Anime, Video Games, Combat Sports, and Mythology. He is fascinated by felines and loves to trek, read, write, click and play.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #3 The vanishing Curator - Game Studies India Adda (Game Studies India Adda, 2020)
Playing back to the Empire, in videogames, is rife with tensions. The imperialist sentiment inherent in reverse-colonist discourse featured in most strategy-based videogames like Europa Universalis IV, where the player could conquer Europe playing for the Marathas, has been noted by Souvik Mukherjee (2017) as playing into the colonial logic while futilely trying to challenge it. Studio Oleomingus, an Indian two-man game studio, is one of the few involved in a different experiment. Their mythical game Somewhere, chronicling a postmodernist search for identity and narrative in the forgotten city of Kayamgadh, has generated significant spin-offs into its universe. With attention to one such spin-off, I will focus critical attention on the issue of the postcolonial gaming of the Museum in A Museum of Dubious Splendors. I will examine the New Museological implications of A Museum of Dubious Splendors, keeping in mind Museologist Eilean Hooper-Greenhill’s assertion of museums embodying “the power to name, to represent common sense, to create official versions, to represent the social world, to represent the past” (Hooper-Greenhill 2001: 2). Oleomingus’ own description of A Museum, as an adaptation of edited, mangled, contested short stories by a fictional Urdu writer, Mir Umar Hassan, eschews the linear narrative production of the colonial museum for a game of meanings, where the player enters rooms according to his choice and constructs his/her own “quiet game about prosaic objects and spurious histories.” ("A Museum" 2018) The paper would take this into account and examine the reconceptualization of the museum space with respect to James Clifford’s sense of museums being “contact zones”: A Museum’s lack of any curator, with its curious blend of colonial and native tales and banal objects defamiliarised by “spurious histories” lends itself to questions of playing the Empire back according to a different episteme, through subaltern histories that the colonial museum space silenced. Paying close attention to the question of postcolonial spatiality in this game, I will analyze the historiographical implications of these identity-scatterings and recuperations at constant play in the structure of the game. Keywords: Museum Studies, Thing Theory, Game studies, Marginal identity, Postcolonial Studies
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Japanese Video Games and Comics in Singapore: Issues in Popularization, Localization and their Implications - Ng Wai-ming, Benjamin (N.D., 1999)
OCLC: 882102421
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Talk #12: Geoffrey Fernandez - Game Studies India Adda (Game Studies India Adda, 2021)
Counter-Hegemonic Representations of Japanese Cultural Icons in Sekiro Abstract: Through fictional or non-fictional narratives, media representations of the past communicate specific interpretations, which lets users negotiate the past's prospective meanings. Additionally, these cultural constructions of the past are produced and disseminated in the present. Hence, the existing hegemonic power relations influence the depiction and recognition of cultural communities in the construction of the past. Therefore, the approach to framing cultures in pop-culture representations becomes a preponderating factor in how people perceive such cultures and periods. Sekiro: Shadows Die Twice, at first glance, can be considered as a game that follows the same vein of exploiting the western craze for the ninja archetype, as seen in its predecessors like the Onimusha and Tenchu series. However, it takes a bold stance against the persisting ‘self-Orientalist’ framework by reclaiming the ninja myth from marketized exoticization. Borrowing from Said’s theory of Orientalism, I would first like to analyze the existing self-Orientalism in depicting and marketing Japanese cultural icons. I would then like to highlight how this game is not an exoticized cultural artefact and further discuss the implications of such a portrayal in the contexts of representation and authenticity. I conclude that by undercutting innate stereotypes and using inherently Japanese characters, the game reappropriates the agency to depict Japanese cultural icons, from a non-Oriental, non-exoticized viewpoint. Thus, Sekiro: Shadows Die Twice becomes a stand-out in the video game industry in this respect. Bio: Geoffrey Fernandez is a PhD candidate at the Department of Humanities and Social Sciences at the Birla Institute of Technology and Science Pilani, Pilani campus. His doctoral research examines the use of culture, mythology, and folklore in video games.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Lure of Pokémon: Video Games and the Savage Mind - Nakazawa, Shin'ichi (Japan Publishing Industry Foundation for Culture, 2019)
From its humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokémon GO. In the work, Nakazawa Shinichi argues that the Pokémon worldview is the best contemporary example of Claude Lévi-Strauss's "savage mind" (la pensée sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature.
Section: 1 v. (129 p.) : illustrations, couv. illustrations en coul. ; 22 cm
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Section: ix, 121 pages : illustrations ; 22 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Transnational Contexts of Culture, Gender, Class, and Colonialism in Play: Video Games in East Asia - Pulos, Alexis; Lee, S. Austin (Palgrave Macmillan, 2016)
This book examines the local, regional and transnational contexts of video games through a focused analysis on gaming communities, the ways game design regulates gender and class relations, and the impacts of colonization on game design. The critical interest in games as a cultural artifact is covered by a wide range of interdisciplinary work. To highlight the social impacts of games the first section of the book covers the systems built around high score game competitions, the development of independent game design communities, and the formation of fan communities and cosplay. The second section of the book offers a deeper analysis of game structures, gender and masculinity, and the economic constraints of empire that are built into game design. The final section offers a macro perspective on transnational and colonial discourses built into the cultural structures of East Asian game play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The Playing Fields of Empire: Empire and Spatiality in Video Games - Mukherjee, Souvik (Journal of Gaming & Virtual Worlds, 2015)
As in historical accounts, empire in video games too is concerned with the acquisition of geographical space. Like the splash of red marking the stretch of the British Empire on Victorian world maps, video games that let one play at empire are also obsessed with stamping the imperialist authority of ‘your’ nation on their in-game maps. Video game empires too work on the necessary logic of spatial expansion connected with which is the necessity to remove the ‘fog’ which prevents the player’s ‘line of sight’ from accessing information about surrounding areas. The focus on cartography and surveying in British Raj India is a useful comparison. Although much scholarship exists around the representations of the spatiality of Empire in more traditional media, there is little that addresses the video game representations of Empire. This article is about the representation and experience of space in conceptions of Empire vis-à-vis in empire-building video games, as understood in terms of both cartography and the lived experience of space. It argues that although empire-building video games are largely framed within the western imperialist discourses, the very nature of gameplay itself challenges these set notions – in a way remediating the ambiguity and anxieties of the representations of empire and its spatial constructs in earlier media.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Egoshooting in Chernobyl: Identity and Subject(s) in the S.T.A.L.K.E.R. Games - Mukherjee, Souvik (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
The issue of identity formation when playing an avatar in a video game has recently become perceived as both increasingly complex and contentious. Game critics argue both for and against the apparent seamlessness in the identity formation in video games. However, while the case against seamlessness builds up with respect to other gaming genres, first-person shooters (FPS) are often still singled out as best representing this first-person identification whereby players were supposed to be totally immersed in their avatars while they played the game. In the light of recent research, this chapter builds on earlier research to reveal further problems in assuming a seamless merging of identity even in the FPS. It argues that the very conception of subjectivity has always been problematized through the FPS, and that the genre itself self-consciously keeps pointing this out. As an example of the latter, the chapter focuses on the S.T.A.L.K.E.R. video games to show how FPS games prompt players to question their in-game identity(ies) because the playing subject, instead of being a fixed entity, is hard-wired into the process of exploration that constitutes gameplay.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Beautiful Fighting Girl - Saitō, Tamaki; Azuma, Hiroki (University of Minnesota Press, 2011)
From Nausicaa to Sailor Moon, understanding girl heroines of manga and anime within otaku culture.
OCLC: 897044808
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Creative Industries Across Cultural Borders: The Case of Video Games in Asia - Tschang, Ted (Creative Economies, Creative Cities: Asian-European Perspectives, 2009)
This chapter examines the relationship between culture, economics and policy within the creative industries (which for the purposes of this paper, are assumed to be equivalent to the cultural industries), and their manifestation in Asia. Addressing any one of these three issues is a challenge in itself, but addressing all three of them together raises the complexity even further. Early writers on the “creative economy” have noted how it works differently from the traditional economy (Florida 2002; Howkins 2001).1 Culture is vitally important to understanding how creative industries develop, but the role of culture in shaping national competitive advantage is not that clear. The same can be said for policy, and a discussion of the triad can be quite convoluted. Having said that, all three levels are still very relevant to the proper description of a creative industry — as I will show in this chapter.This paper attempts to address this triad of issues primarily with a production-and-innovation-oriented view of industrial organisation, bringing in creativity, culture and policy where possible. I shall do this primarily through the lens of one sector in particular — the video games industry — in which Asia has been investing heavily lately, and in which Japan has been an early leader. I will also provide a limited focus on the animation sector for comparative purposes. I will first provide a summary of how creative production in video games occurs in the US, followed by an examination of how Asian patterns compare. In particular, I am interested in whether individual and industrial level creativity differs in Asia. Within Asia, more detailed cases of the Chinese online games industry and the Philippine animation industry will be discussed, but relevant observations are also drawn from general knowledge and a literature review of Japan, Korea and Singapore, as well as interviews which corroborate those observations.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games in Asia - Ng Wai-ming, Benjamin (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

ゲーム的リアリズムの誕生 ; Gēmu-teki riarizumu no tanjō - Azuma, Hiroki (Kōdansha, 2007)
Section: 1 vol. (339 p.) : ill. en n. et b. ; 18 cm.
Keywords: 1-Jeux vidéo; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer

Japanese Video Games in Singapore: History, Culture and Industry - Ng Wai-ming, Benjamin (Asian Journal of Social Science, 2001)
Globalization of Japanese popular culture is reshaping the global cultural landscape. Some forms of Japanese popular culture (such as video games animation and sushi) are well-received internationally, whereas others (such as pop music, films and TV dramas) are only popular in Asia. Of all forms of Japanese popular culture, video game is perhaps the most powerful due to its strong universal appeal. It has dominated the world market since the mid-1980s. This article uses Singapore as a case study to demonstrate the global popularization of Japanese video games. There has been a boom of Japanese popular culture in Singapore in the 1990s. In particular, Japanese video games, comics and animation have become an integral part of youth culture in Singapore (Ng, March 2000: 234-246; Ng, May 2000: 44-56; Ng, June 2000: 1-14). Video game is a neglected topic in cultural studies. Although there are some basic studies of Japanese video games in the Western world (Hayes & Disney, 1995; Herz, 1997; Kinder 1991; Monopolies, 1995; Sheff, 1993), its impact in Asia is largely unknown. This article is a preliminary study of the Japanese video game culture and industry in Singapore from historical and socio-cultural perspectives, focusing on consoles, games and players. Based on interviews, questionnaires and data from newspapers and magazines, this research aims at pro viding a general overview of the history and impact of Japanese video games in Singapore. All the data and analyses are basic and this is beyond the scope of this paper to discuss any particular issue or theory in details. This paper consists of four sections. The first three sections outline the development of home video game consoles, handheld electronic games and game arcades respectively. The concluding section pinpoints the characteristics of the video
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

電脳遊戯の少年少女たち ; Dennō yūgi no shōnen shōjotachi - Nishimura, Kiyokazu (Kōdansha, 1999)
Section: 212 pages : illustrations ; 18 cm
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer